Impact of P‐gp inhibition on systemic exposure of pralsetinib and dosing considerations - Julia Suchomel; Priya Agarwal; Doreen Anders; Kevin Hughes; Yang Tang; Rucha Sane; Astrid Scalori; Sunil Sharma; Sravanthi Cheeti (Wiley, 2024)
Abstract A study to determine the impact of cyclosporine (Neoral), an inhibitor of P‐gp, on the pharmacokinetics of pralsetinib (trade name GAVRETO®) was conducted in 15 healthy adult volunteers. A single 200 mg dose of pralsetinib was administered orally alone and in combination with cyclosporine with a 9‐day washout between treatments. Co‐administration with cyclosporine resulted in a clinically relevant increase in pralsetinib maximum plasma concentration (Cmax) and area under the plasma concentration-time curve extrapolated to infinity (AUC0-∞) with associated geometric mean ratios (GMRs) and 90% confidence intervals (CIs) of 148% (109, 201) and 181% (136, 241), respectively. These findings provide insight into concomitant dosing of pralsetinib with inhibitors of P‐gp given the increases in pralsetinib exposure observed when administered with cyclosporine. Based on these results, co‐administration of pralsetinib with P‐gp inhibitors is not recommended. In the event that co‐administration cannot be avoided, it is recommended that the dose of pralsetinib be reduced.